Cognitive Load and Sentence Processing: How EFL Learners Comprehend Complex Clauses in Academic Texts - Rahayu Wulandari; Khairunnisa Khairunnisa; M.Habib Rifki Nasution; Yani Lubis (International Journal Multidisciplinary Science, 2026)
This study examines how cognitive load influences sentence processing in the comprehension of complex clauses among English as a Foreign Language (EFL) learners. It aims to explore learners’ perceptions of sentence complexity, their strategies in managing comprehension difficulties, and their awareness of the cognitive effort involved in reading academic texts. Using a qualitative phenomenological approach, ten English Education students from a university in Medan, Indonesia, participated in reading tasks containing complex academic sentences. Data were collected through think-aloud protocols and in-depth semi-structured interviews, then analyzed using discourse and thematic analysis to identify linguistic and cognitive patterns. The results indicate that complex sentence structures impose high cognitive demands, especially when multiple clauses and dense syntactic constructions are present. Learners with limited working memory capacity experienced slower reading, repeated rereading, and fragmented comprehension. To cope with these challenges, they employed strategies such as segmentation, rereading, translation, and note-taking, which helped reduce processing strain but did not fully enhance efficiency. The study concludes that comprehension difficulties arise from the interaction between cognitive load, sentence complexity, and working memory limitations, emphasizing the importance of instructional approaches that align linguistic input with learners’ cognitive capacities.